2021
DOI: 10.1021/acsami.1c00095
|View full text |Cite
|
Sign up to set email alerts
|

Closed-Loop Nanopatterning of Liquids with Dip-Pen Nanolithography

Abstract: The ability to reliably manipulate small quantities of liquids is the backbone of high-throughput chemistry, but the continual drive for miniaturization necessitates creativity in how nanoscale samples of liquids are handled. Here, we describe a closed-loop method for patterning liquid samples on pL to sub-fL scales using scanning probe lithography. Specifically, we employ tipless scanning probes and identify liquid properties that enable probe−sample transport that is readily tuned using probe withdrawal spee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 32 publications
(47 reference statements)
1
11
0
Order By: Relevance
“…[ 35 ] Here, we utilized a tipless AFM cantilever to capture a resin droplet and then pattern sub‐picoliter quantities of the resin while tracking the amount of resin on the probe using inertial sensing. [ 36 ] Specifically, the mass and location of the loaded resin drop were determined by measuring the frequency of the first two vibrational resonance modes in between each step of the patterning process. As shown in the schematic ( Figure a), the durable resin was first nanopatterned on a hydrophobic silicon wafer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 35 ] Here, we utilized a tipless AFM cantilever to capture a resin droplet and then pattern sub‐picoliter quantities of the resin while tracking the amount of resin on the probe using inertial sensing. [ 36 ] Specifically, the mass and location of the loaded resin drop were determined by measuring the frequency of the first two vibrational resonance modes in between each step of the patterning process. As shown in the schematic ( Figure a), the durable resin was first nanopatterned on a hydrophobic silicon wafer.…”
Section: Resultsmentioning
confidence: 99%
“…The mass of loaded resin on the cantilever was quantified according to the two‐mode inertial mass sensing method. [ 36 ] All the resin features were patterned with an attractive set point of 300 nN, 1 s dwell time, 1 µm s −1 approach speed, and 10 µm s −1 retraction speed. The mass of each patterned feature was determined by measuring the thermal PSD of the cantilever after each patterning force‐displacement curve.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, the authors found a mass resolution limit of about 5 pg in their set-up which resulted in a resolution of about 5 fL considering a water-based ink. A breakthrough has been recently reported by Saygin and coworkers, 68 who firstly demonstrated real-time closed-loop control whilst patterning droplets with volumes on the pL to sub-fL scales reaching resolutions down to 20 aL (Fig. 1).…”
Section: Solution Dispensing: How To Control the Droplet Volume?mentioning
confidence: 93%
“…These techniques are usually based on scanning probe techniques (SPM) such as scanning tunneling microscopy (STM), , atomic force microscopy (AFM), scanning electrochemical microscopy (SECM), etc. By using the nanometer-sized tip electrodes, AFM and STM were demonstrated to fabricate metallic nanostructures, cluster arrays, or even single atom patterns on conductive substrates by electrochemical deposition. If a micro-/nanometer-sized micropipette is adopted as the scanning tip to construct a microcell, recently EC-SPMs have been well developed as an effective electrochemical 3D-printing technique working in an ambient environment. These are indeed direct-writing techniques and are very useful for the research of principle verification and custom-tailored fabrications. The machining accuracy depends actually on the size of the scanning probe even if the electrochemical reaction is coupled by a mass transfer process and consequently, there exists a diffusion layer on the electrode surface. Ultrashort voltage pulses (USVP) has been introduced in 2000 to improve the machining accuracy further. , Nevertheless, EC-SPM direct-writing techniques have been suffered from the low efficiency because of the point-by-point machining mode.…”
Section: Introductionmentioning
confidence: 99%